Gaya Kepemimpinan Kepala Sekolah dalam Peningkatan Kinerja Guru Pendidikan Agama Islam di Sekolah Menengah Pertama Kabupaten Aceh Besar - Saifullah Saifullah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2016)
The school principal is prioritizing the interests of tasks in school, especially in improving teacher performance. The purpose of this study was to determine how the style of principal leadership in improving the performance of Islamic religious education teachers in secondary schools the district of Aceh Besar. This research was conducted at the junior high school environment Aceh Besar District Education Office by using qualitative research through observation. The source of the data in this study is the headmaster and teacher of Islamic education in junior high school environment Aceh Besar District Education Office. In addition to source samples of data taken by the author are the documents relevant to the style of school leadership in improving the performance of Islamic education teachers in junior high school environment Aceh Besar District Education Office. Data collected through research instruments such as interviews, observation, documentation and studies in processing and analyzing the data the author uses triangulation techniques. Based on the research results in Junior High School environment of the District Education Office of Aceh Besar findings suggest that efforts are being made by the principal in improving the performance of teachers of Islamic education, including by providing training and giving them the opportunity to develop its human resources through the container MGMPs Religious Education Islam as well as give them the opportunity to attend trainings organized by the Regional Office of the Ministry of Religious provincial and organized by the Office of Religious Affairs of Aceh Besar district for the sake of their personal development in order to carry out the teaching and learning process subjects of Islamic education in accordance with what has been outlined in the syllabus and RPP subjects of Islamic Religious Education